System of psychological assistance in self-realization of the personality of the athletes: domestic and foreign approach - Sokolovskaya, S. V.; Ulyaeva, L. G.; Ulyaeva, G. G.; Orlova, E. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to study domestic and foreign approaches to the system of psychological assistance in the self-realization of the athlete's personality at the stages of many years of sports training.